Bulletin Awepa. (Amsterdam : AWEPA - European Parliamentarians for Africa.)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: Prins Hendrikkade 48 G, 1012 AC Amsterdam
Engels
Periodiek